1989
DOI: 10.3171/jns.1989.70.1.0041
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intracranial meningiomas

Abstract: The authors report 14 cases of multiple intracranial meningiomas representing 1.1% of all meningiomas operated on at their hospital in the past 35 years. Differentiation of multiple meningiomas, especially from meningiomatosis, must be strict. Since the introduction of computerized tomography scanning, the frequency of these cases has risen from 0.58% to 4.5% in the authors' meningioma series. Despite the multiplicity of sites, multiple meningiomas do not differ in prognosis from benign solitary meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 14 publications
2
33
1
4
Order By: Relevance
“…The cerebral convexity, parasagittal-falx region, and sphenoid ridge are common sites of occurrence of multiple meningiomas (3,12,17,21) and these sites are different from the locations of the mass lesions in our case. Because of the growing number of reports of such multiple pseudotumors associated with IgG4-related disease, we think that special attention to this disease entity is needed in the differential diagnosis when multiple dural-based tumors are observed.…”
Section: Case Reportcontrasting
confidence: 62%
“…The cerebral convexity, parasagittal-falx region, and sphenoid ridge are common sites of occurrence of multiple meningiomas (3,12,17,21) and these sites are different from the locations of the mass lesions in our case. Because of the growing number of reports of such multiple pseudotumors associated with IgG4-related disease, we think that special attention to this disease entity is needed in the differential diagnosis when multiple dural-based tumors are observed.…”
Section: Case Reportcontrasting
confidence: 62%
“…The current WHO grading system comprises three grades as follows: most meningiomas are slow growing, are generally considered benign tumors, and correspond to grade I (typical meningiomas); about 10% of cases are classi®ed as grade II (atypical) or anaplastic/malignant (grade III), exhibiting more aggressive clinical behaviour, with a higher risk of recurrence when compared to typical grade I meningiomas (Kleihues et al, 1993). These neoplasms are usually sporadic, but a few families have been described with multiple tumors inherited in an autosomal dominant fashion (Memon, 1980;Battersby et al, 1986;Butti et al, 1989;Domenicucci et al, 1989), and they also occur in as many as half of the patients with the dominantly inherited familial neuro®bromatosis type 2 syndrome (NF2) (Martuza and Eldridge, 1988). Using positional cloning approaches, the candidate gene for NF2 has been isolated from chromosome 22q12 region (Rouleau et al, 1993;Trofatter et al, 1993), and mutations have been observed in both germ-line of NF2 patients and in about 30% of sporadic meningiomas Lekanne-Deprez et al, 1994;Merel et al, 1995;Papi et al, 1995;De Vitis et al, 1996;Harada et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In this particular series, all the patients were female and underwent CT before operation. Domenicucci et al [7] reported 14 cases of multiple intracranial meningiomas representing 1.1% of all meningiomas operated on at their hospital in the past 35 years. In their series, they noted that since the introduction of CT scanning, the frequency of these cases has risen from 0.58% to 4.5% in the authors' meningioma series.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, multiple meningiomas do not differ from the solitary types [7]; however, the simultaneous occurrence of different grades of malignancy in the nodules is observed in one-third of multiple meningiomas [12]. The most common histological types reported in multiple meningiomas include psammomatous, fibroblastic, meningothelial, and transitional types [13].…”
Section: Discussionmentioning
confidence: 99%